Effectiveness of Guidance and Counselling Programme in Reducing Ethical Decline among Secondary School Students During Times of Socio-Economic and Political Challenges in Kwara State - Michael, Ifeoluwa; Abisoye, Faysol (Buletin Konseling Inovatif, 2025)
This study examined the effectiveness of guidance and counselling programs in reducing ethical decline among secondary school students during periods of socio-economic and political challenges in Kwara State. Four research questions guided the study, along with one hypothesis. Using a descriptive survey design, data were collected from a population of 3,780 Senior Secondary Three (SS3) students in Kwara State. A sample of 300 students, selected through stratified random sampling from six secondary schools, participated in the study. A self-developed structured questionnaire titled "Effectiveness of Guidance and Counselling Programs in Reducing Ethical Decline Questionnaire (EGCREDQ)" was utilized for data collection, with a reliability coefficient of 0.75 determined by Cronbach’s Alpha. Descriptive statistics (mean, standard deviation, and percentages) analyzed the research questions, while Pearson’s Product Moment Correlation tested the hypothesis. The findings revealed a significant prevalence of ethical decline, including behaviors such as dishonesty and violence. The guidance and counselling programs in place were found to be insufficient, hindered by inadequate resources, unqualified counsellors, and poor implementation structures. Furthermore, key challenges identified included stigma associated with seeking counselling, limited parental involvement, and counsellors being overburdened with other responsibilities. These barriers have limited the effectiveness of the programs in addressing the socio-economic and political challenges faced by students. It was recommended that functional guidance and counselling centers be established in all schools, equipped with trained counsellors and adequate resources, to address these issues effectively.